MICASA: a randomized trial using biochemical markers and cardiac magnetic resonance imaging. (June 2011) - van Gaal, William J; Banning, Adrian P
Patients with coronary artery disease who undergo revascularization are prone to periprocedural myocardial injury. Although this may reflect procedural complications, it can occur in an uneventful routine procedure. This injury is reflected by increases in blood biomarkers, and it occurs during both coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI). Recent studies using late gadolinium enhancement cardiac magnetic resonance (LGE-CMR) imaging have demonstrated that higher elevations of creatine kinase-MB and troponin I reflect new myocardial necrosis. LGE-CMR is a noninvasive, radiation-free technique that offers considerably higher spatial resolution than alternative forms of cardiac imaging (e.g., positron emission tomography and stress single-photon emission computed tomography). LGE-CMR provides accurate quantification of even small areas of necrosis, allowing for direct comparison of the incidence and amount of periprocedural injury between different revascularization strategies. This article reports on the Myocardial Injury following Coronary Artery Surgery versus Angioplasty study, the first study to directly compare periprocedural injury as defined by serial CMR imaging before and after revascularization with either PCI or CABG.